Uterine Artery Doppler Velocimetry During Individually Prescribed Exercise in Pregnancy. Issue 4 (October 2018) - Szymanski, Linda M.; Kogutt, Benjamin K.
Abstract : OBJECTIVE: To evaluate uterine artery blood flow in response to typical exercise sessions performed in pregnancy in accordance with the current recommendations from the American College of Obstetricians and Gynecologists and the U.S. Department of Health and Human Services. METHODS: This prospective cross-sectional study measured uterine artery Doppler velocimetry in healthy pregnant women after individually prescribed exercise, including 1) moderate-intensity exercise (40–59% of heart rate reserve) in both nonexercisers and regular exercisers and 2) vigorous-intensity exercise (60–84% of heart rate reserve) in women who regularly engage in exercise. Resting uterine artery Doppler measures were obtained after a 20-minute fetal heart tracing; then the exercise session was performed. Immediately after the exercise session ended, the participants returned to the semirecumbent, leftward tilt position for ultrasound examination. Uterine artery measures were obtained 3.4±0.9 minutes (mean±SD) postexercise. RESULTS: Forty-five healthy pregnant women participated in the study: 30 regular exercisers and 15 nonexercisers. For the moderate-intensity session, mean gestational age was 31.1 and 31.7 weeks for the exercisers and nonexercisers, respectively. Mean uterine artery Doppler indices (pulsatility index, resistance index, systolic/diastolic ratio) did not significantly change with exercise. For the vigorous-intensity session, the average gestational age was 31.5 weeks. After vigorous activity, all mean uterine artery Doppler indices showed reductions postexercise, for example, pulsatility index decreased from 0.63±0.12 to 0.58±0.12 ( P =.04). CONCLUSION: Individually prescribed exercise according to guidelines for pregnant women does not adversely alter uterine artery Doppler values, suggesting that uterine blood flow is not reduced as a result of exercise. Abstract : Exercise performed per current pregnancy recommendations does not reduce uterine artery blood flow as estimated by Doppler velocimetry.